PKM Penggunaan Artificial Intelligence (AI) dalam Deep Learning pada Guru SMK Ma’arif NU 01 Limpung Kabupaten Batang - Zuhri, Muhammad Saifuddin; Shodiqin, Ali; Murtianto, Yanuar Hery; Ardiyanto, Asep (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
Deep learning in education is an approach that emphasizes deep and meaningful understanding. In addition, deep learning also refers to an Artificial Intelligence (AI) method that enables computers to process data intelligently. In the field of education, this approach encourages active student engagement in the learning process, where they are guided to connect theoretical knowledge with real-world situations. This activity aims to assist teachers at SMK Ma’arif NU 01 Limpung, Batang, in implementing Artificial Intelligence (AI) in deep learning-based instruction. The expected outcome of this activity is that teachers receive training on the use of AI in education, covering both theoretical understanding and practical skills, including the use of ChatGPT and Wolfram Mathematica. The training is conducted in groups using an andragogical approach. The methods used include question and answer sessions, lectures, discussions, demonstrations, exercises, and hands-on practice. The training materials consist of 25% theory and 75% practice. The activity takes place in the auditorium of SMK Ma’arif NU 01 Limpung, Batang. There are 55 teachers participating in this training.